The Specificity of Euphemisms as Linguistic Units - Abdukarimovna, Kabilova Sayyora; qizi, Abduvoxidova Dilnoza Boborahim (European Journal of Life Safety and Stability (2660-9630), 2022)
This article summarizes the distortion of euphemism and provides information about the unity of euphemism in the works of Uzbek, Russian and English linguists. We should consider these symbols semantically and pragmatically.